Development of Communication Models Mother-Daughter-Dyads about Sex Education in Prevention of Teenage Pregnancy Research and Development (R&D) - Putri Eka Sejati; Shanty Natalia; Anggrawati Wulandari (Universitas STRADA Indonesia, 2023)
Background: Teenage pregnancy contributes significantly to the cause of mother death and baby death in Indonesia. A total of 9.5% of teenage girls aged 15-19 years have been married, pregnant and giving birth. One of the causes of high teenage pregnancies is the lack of sex education. The family is the first social environment to build character and values in adolescents. It is crucial to create a climate conducive to open discussion between parents and daughter about sex education. Still, in reality, many parents have not provided sufficient information to their children about how to prevent unsafe sex among teenagers and view taboo as one of the causes of the lack of communication among parents and daughters about sex. Purpose: This study aims to develop an effective communication model between mothers and teenagers on educational sex. Methods: This research uses the Research and Development (R&D) way that is the research method used to produce a particular product and test the effectiveness of the product. Results: Identification of sexual communication between mothers and daughters concluded that both daughters and their mothers still had difficulty communicating related to sexual education. The results of the need assessment carried out by FGD have found formulations that respond to the need for models used in the enhancement of sexual communication between mothers and daughters. Conclusion: The model developed in this study showed results at the evaluation stage that there was an improvement in parents’ ability to conduct sexual communication using effective communication patterns.